DIGITAL HISTORY AND ARCHIVES AS LEARNING MEDIA TOWARDS TRANSFORMATIVE EDUCATION IN THE POST-PANDEMIC ERA - Labibatussolihah Labibatussolihah; Nour Muhammad Adriani; Nana Supriatna (Jurnal Pendidikan Ilmu Sosial, 2022)
The end of the 20th century was marked by euphoria over the development of internet technology such as the world wide web, which brought changes to scientific development including accessibility of historical sources and its use. This shift supports new adaptations as well as challenges conventional archival models, while opening opportunities for these digitized documents in history learning. However, the conversion or digitization of archives in Indonesia is slow, let alone its use for education, especially history education. This paper will take some experiences from countries that have digitized archives and adapt them in the history learning process as a real-world real-time experience. Two countries, the Netherlands and Australia, will be compared to see how they implement these strategies and how Indonesia can adopt a similar model for it. Further, five teacher candidates were involved as informants in interviews regarding their effort to incorporate digital historical sources in the learningfrom-home activities. A qualitative approach was used to see the extent to which the readiness of technical and non-technical aspects of the implementation of real-world and real-time-experience learning model in history education. While the review shows how promising the digital history and historical sources in the developed countries is, Indonesia is not ready enough for its usage due to some issues. These challenges will be discussed further. Keywords: digital history, real